2023
DOI: 10.3390/disabilities3020012
|View full text |Cite
|
Sign up to set email alerts
|

Use of Overground Supported-Stepping Devices for Non-Ambulant Children, Adolescents, and Adults with Cerebral Palsy: A Scoping Review

Abstract: Individuals with cerebral palsy functioning at Gross Motor Function Classification System (GMFCS) levels IV and V are unable to use hand-held walkers and require supported-stepping devices with trunk and pelvic support to allow overground stepping in natural environments. This scoping review explored what is known about the use of supported-stepping devices with individuals functioning at GMFCS IV or V. Comprehensive database and hand searches were completed in December 2022. Of 225 unique citations, 68 met th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 97 publications
0
28
0
Order By: Relevance
“…Group experimental, observational and qualitative study evidence was mainly moderate or high quality, other than research on hip stability, which is still limited, as indicated in Section 3. This manuscript is not a scoping or systematic review, and readers are directed to the two original review publications [21,22] for details regardevidence level, quality and risk of bias analyses. Two different theoretical frameworks were used in the analysis of this evidence to create an integrated model, which is open to discussion.…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Group experimental, observational and qualitative study evidence was mainly moderate or high quality, other than research on hip stability, which is still limited, as indicated in Section 3. This manuscript is not a scoping or systematic review, and readers are directed to the two original review publications [21,22] for details regardevidence level, quality and risk of bias analyses. Two different theoretical frameworks were used in the analysis of this evidence to create an integrated model, which is open to discussion.…”
Section: Limitationsmentioning
confidence: 99%
“…Supported standing and stepping devices can promote functioning, fitness and overall health, emotional development, inclusion and participation in home and school settings for children with non-ambulant CP [ 21 , 22 ]. Development of independent standing or stepping without the devices is not an expectation, and power mobility is the focus for efficient functional mobility for children at GMFCS levels IV/V, especially in community settings [ 3 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children who are 50% delayed in motor skills, or with a HINE score <40 [70], are highrisk of functioning at Gross Motor Function Classification System (GMFCS) IV and V [121] and may fit the profile of severe hypotonia. Recommendations for children with CP, GMFCS IV, and V should be implemented, including early introduction of adaptive seating [122,123], supported standing [124], stepping [125], and power mobility devices [126][127][128], to promote ON-Time positioning and mobility experiences [129]. Consideration should also be given to monitoring hip health and inclusion in surveillance programs, since non-ambulant children with hypotonia are also at high risk for hip displacement [130,131].…”
Section: Recommendations For Clinical Practicementioning
confidence: 99%